Protracted tuberculous empyema necessitans following intercostal drainage tube insertion - Kohli, Saksham; Agrohi, Jhalak; G. K., Adarsha; Agrohi, Daksh (International Journal of Research in Medical Sciences, 2023)
Empyema necessitans (EN) is a rare long-term sequela of poorly or untreated empyema thoracis, characterized by the dissection of pus through the soft tissues and skin of the chest wall, ultimately forming a fistula between skin and pleural cavity. We herein present a male patient in his late 30s, a known case of tuberculosis (TB) on anti-tubercular therapy (ATT) under directly observed treatment short-course (DOTS), who recently came with complaints of backache for 3 days. Chest X-ray showed a massive pleural effusion, in view of which an intercostal drainage tube (ICD) was inserted and 1.5 L of pleural fluid was drained. An ultrasound (USG) back done revealed subcutaneous collection with communication to pleural space, which resolved after pleural fluid drainage. As there was a persistent communication between pleural space and right-sided subcutaneous plane with a massive effusion i.e., EN, he was advised to undergo thoracotomy with decortication and resection of communication which he underwent successfully. This case is presented for its rarity with atypical presentation.